KEBERHASILAN BP3K RAMAN UTARA KABUPATEN LAMPUNG TIMUR DALAM LOMBA PRESTASI TINGKAT PROVINSI TAHUN 2015 - Ayu Okriani; Indah Nurmayasari; Dewangga Nikmatullah (Lampung University, 2017)
This research aimed to analyze the implementation race of achievement BP3K in Lampung Province, scores and aspects of the North Raman BP3K in 2015, and the income of farmers assisted by The North Raman BP3K East Lampung Regency. This research was conducted in North Raman Subdistrict East Lampung District. Respondents of this research were 53 peoples, that consist of 10 agricultural extension workers who were selected by purposive sampling method and 43 farmers who were selected by simple random sampling. Implementation race of achievement BP3K in Lampung Province was analyzed descriptively. The result of this research showed that achievement BP3K votes in Lampung Province in 2015 conducted by the method of selection requirements, administrative, and field observations. Aspects of assessment were analyzed descriptively using tabulation. Aspects of assesment includes: facility, infrastructure, human resources, operational management, and activities. The five aspects were scored between 2 to 861. The result of research on The North Raman BP3K provisionally got a score of 783 points, and include the category successfully. Assisted farmers income increased by 3.9 percent a year before and after The North Raman being achivement BP3K.Key words: assisted, achievements, BP3K